Effects of photoperiod sensitivity genes Ppd‐B1 and Ppd‐D1 on spike fertility and related traits in bread wheat - Ramirez, Ignacio Abel; Abbate, Pablo Eduardo; Redi, Ignacio W.; Pontaroli, Ana Clara (Wiley Online Library, 2018)
Increasing grain yield is a key breeding goal in bread wheat. Several authors have suggested that a spike fertility index (SF), that is the quotient between grain number per unit spike (GNS) and spikechaff dry weight (SCDW), could be used as a yield‐related selection criterion, especially if molecular markers were available. Here, the effects of Ppd‐B1 and Ppd‐D1 genes on SFm, GNSm and SCDWm (measured at maturity) and the relationship between these variables were analysed in field experiments carried out during three crop seasons at Balcarce, Argentina, on an association mapping population of 100 bread wheat cultivars of diverse origin released in Argentina between 1927 and 2010. Results show that both Ppd‐B1 and Ppd‐D1 are associated with SFm with similar effects. Cultivars with insensitive alleles at both genes showed a mean SFm 9.2% greater than those with sensitive alleles at both genes; at each gene, difference in SFm between insensitive and sensitive alleles was ~4.5%. In turn, each gene showed a differential effect on GNSm and SCDWm, as Ppd‐B1 was more related to SCDWm, whereas Ppd‐D1 was only related to GNSm. Although more research needs to be carried out in order to ascertain the physiological pathway by which these genes affect spike fertility, this study represents a first approximation in order to elucidate the molecular and genetic basis underlying SF and related physiological traits.